Expression of π-class glutathione S-transferase: two populations of high grade prostatic intraepithelial neoplasia with different relations to carcinoma. Issue 3 (1st June 2000) - Montironi, R; Mazzucchelli, R; Stramazzotti, D; Pomante, R; Thompson, D; Bartels, P H
Abstract : Background/Aims —Patients with high grade prostatic intraepithelial neoplasia of the transition zone appear to be at increased risk of developing prostatic carcinoma, although not to the same degree as patients with high grade prostatic intraepithelial neoplasia of the peripheral/central zone. Previous investigations have shown loss of expression of π-class glutathione S-transferase (GST-π; an enzyme that protects against electrophilic carcinogens) in prostatic carcinoma and in high grade prostatic intraepithelial neoplasia. The aim of this study was to compare the expression of GST-π in high grade prostatic intraepithelial neoplasia of the transition zone with that in high grade prostatic intraepithelial neoplasia of the peripheral/central zone (that is, non-transition zone). Methods —Immunostaining with the anti-GST-π antibody was performed on 20 high grade prostatic intraepithelial neoplasia samples of the transition zone, either isolated or associated with prostatic carcinoma (groups 1 and 2, respectively; 10 cases each) and on 20 high grade prostatic intraepithelial neoplasia samples of the non-transition zone, either isolated or associated with prostatic carcinoma (groups 3 and 4, respectively; 10 cases each). This study also included six samples of high grade prostatic intraepithelial neoplasia simultaneously present in the transition and non-transition zones and not associated with prostatic carcinoma (group 5). The presence of immunostaining, staining intensity, and the distribution of immunostaining were evaluated in the high grade prostatic intraepithelial neoplasia lesions and in the normal tissue and cancer areas. Results —The GST-π antibody stained the cytoplasm of the cells lining the ducts and acini of normal prostate tissue. Staining was stronger and more diffuse in the basal cell layer than in the luminal (or secretory) cell layer. Immunohistochemical staining with anti-GST-π antibodies failed to detect the enzyme in all prostatic carcinoma foci but one. Two patterns were detected in high grade prostatic intraepithelial neoplasia. One was represented by GST-π staining similar to that of the normal tissue (pattern A). The other deviated from it and was characterised by absence of GST-π expression in the secretory cells and abundant expression in scattered basal cells (pattern B). Pattern A staining was seen more frequently in the transition than in the non-transition zone. Pattern B staining was seen mainly in high grade prostatic intraepithelial neoplasia of non-transition zone associated with cancer. Conclusions —The differential expression of GST-π in the transition and non-transition zones indicates the existence of two populations with the morphological appearance of high grade prostatic intraepithelial neoplasia that might have different associations with carcinoma.